Green Lifestyle among Indonesian Millennials: A Comparative Study between Asia and Europe - Genoveva, Genoveva; Syahrivar, Jhanghiz (Journal of Environmental Accounting and Management, 2026)
Unethical business practices coupled with irresponsible consumption activities come with painful environmental costs. Fortunately, various studies have indicated that ecological concerns are the highest among the millennial generation. The aim of this research is to investigate the factors influencing green lifestyle among Indonesian millennials who live in Asia and Europe. Cultural elements, such as religious passion and spirituality, are also incorporated in this study in order to understand how they influence green intention and lifestyle. To our best knowledge, this is the first comparative study to understand the green lifestyle of Indonesian millennials in the two regions. This study gathered a total of 204 valid respondents. We employed a Structural Equation Modelling method to test our hypotheses. We found that 1) the New Environmental Paradigm is a predictor of green behavior intention 2) religious passion, spirituality and green behavior intention are predictors of green lifestyle. Theoretical contributions as well as managerial implications are offered in this study.